ACTIVE IMMUNIZATION OF MICE WITH THE POLYSACCHARIDES OF PNEUMOCOCCI TYPES I, II AND III - Zozaya, José (The Rockefeller University Press, 1933)
1. Pneumococcus polysaccharides Types I, II and III adsorbed on collodion particles, and Types I and III adsorbed on carbon (norit) are antigenic in mice. 2. Unadsorbed pneumococcus polysaccharide of Type I is antigenic in mice in proper dilution. One preparation of Type II polysaccharide was not antigenic, while another one immunized against Types I and II. Type III polysaccharide was only slightly antigenic against Type III but immunized against Type I. 3. The antigenicity of pneumococcus polysaccharide in optimal dosage is tentatively explained by an adsorption phenomenon taking place in the body in instances in which the polysaccharides had not been adsorbed before injection. 4. The aggressin-like action of large doses of pneumococcus polysaccharides Types I, II and III is further established.